Ant-Man [videorecording (DVD)] - Douglas, Michael, 1944-; Lilly, Evangeline, 1979-; Stoll, Corey, 1976- (Buena Vista Home Entertainment, 2015)
Armed with the astonishing ability to shrink in scale but increase in strength, master thief Scott Lang must embrace his inner-hero and help his mentor, Dr. Hank Pym, protect the secret behind his spectacular Ant-Man suit from a new generation of towering threats. Against seemingly insurmountable obstacles, Pym and Lang must plan and pull off a heist that will save the world.